The Urgency of Notary Involvement in the Process of Destroying Illegal Fishing Evidence to Achieve Legal Certainty and Justice - R. Juli Moertiono (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
Illegal fishing is a serious crime that results in state losses, damage to marine ecosystems, and social injustice for local fishermen. One form of law enforcement carried out by the state is the destruction of evidence in the form of fishing vessels and gear. However, in practice, the process of destroying such evidence still leaves legal issues, particularly regarding legal certainty, accountability, and protection of the rights of related parties. This study aims to analyze the urgency of notary involvement in the process of destroying illegal fishing evidence as an effort to realize legal certainty and justice. The research method used is normative juridical with a statutory and conceptual approach. The results show that notary involvement through the creation of authentic deeds can provide legal certainty, transparency, and strengthen the legitimacy of the action of destroying evidence so that it is in line with the values of substantive justice. Illegal fishing is a serious crime that not only causes economic losses to the state but also damages marine ecosystems and causes social injustice for local fishermen who engage in legal fishing activities. As a form of law enforcement, the state imposes additional criminal sanctions in the form of destroying evidence, particularly vessels and fishing gear used in the crime. However, in practice, the destruction of evidence of illegal fishing still faces various legal challenges, particularly those related to legal certainty, transparency, accountability, and the protection of the rights of the parties involved. This situation has the potential to give rise to legal disputes and undermine the legitimacy of the destruction of evidence. This study aims to analyze the urgency of notary involvement in the process of destroying evidence of illegal fishing as an effort to realize legal certainty and substantive legal justice. The research method used is normative juridical with a statutory approach and a conceptual approach, through a review of laws and regulations in the field of fisheries and notaries as well as relevant legal doctrines. The results of the study indicate that notary involvement through the creation of authentic deeds can provide legal certainty, increase transparency and accountability, and provide legal protection for all interested parties. Thus, notary involvement can strengthen the legitimacy of the policy of destroying evidence of illegal fishing as part of just law enforcement and based on the principles of the rule of law.